Benefits of Progressive Muscle Relaxation Therapy in Reducing Anxiety Levels of Health Workers During the Covid-19 Pandemic - Ayu Pratiwi; Yunike Edmaningsih; Rudi Haryanto; Mohamad Riki Fauzi; Muhamad Eki Syahrudin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The number of Covid-19 cases has increased. Facing this situation, front-liner medical staffs are at risk of experiencing psychological stress. The main causes of their anxiety are about their own health and the spread of their families. Progressive muscle relaxation is a stress management technique to reduce stress. Progressive muscle relaxation can relieve anxiety, stress, or tension. This activity aims to provide online counseling and group activity therapy about progressive muscle relaxation techniques for health care providers of Covid-19 patients. It is expected to reduce the level of anxiety of them. The counseling method uses the power point presentations and the demonstrations of progressive muscle relaxation through the Zoom Meeting application. After conducting counseling and group activity therapy, the anxiety level of medical staffs has decreased.